Pengaruh Kualitas Pelayanan Costumer Service Online Dan Harga Terhadap Keputusan Pembelian Konsumen Pada Aplikasi Belanja Online Shopee di Kota Padang Panjang - Fazli Dermawan; Rose Rahmidani (Universitas Negeri Padang, 2022)
Technological advances facilitate the activities distributed by the community, also having an effect on the electronic commerce business. One among them has a bearing on the Shopee online shopping application. This study aims to see the effect of online customer service quality and price on consumer purchasing on the Shopee online shopping application in Padang Panjang City. This type of study employs a causal associative methodology and is quantitative. People from the town of Padang Panjang who have made purchases using the shopee online shopping app make up the study's demographic. The sample collection technique used purposive sampling with a complete sample of 97 people. The information collection technique during this study used a pursuit questionnaire. Multiple correlation analysis was used to examine the data that had been gathered. The study's findings demonstrate that 1) the quality of online customer service has a significant impact on buying choices on the Shopee online shopping application in the city of Padang Panjang, as indicated by the sig value of 0.000 0.00, and 2) the price has a significant impact on buying choices on the Shopee online shopping application in the city of Padang Panjang, as indicated by the sig value of 0.006 > 0.05.